Transmissibility-based operational modal analysis: Unified concept and its application. (1st October 2022) - Dario Gómez Araújo, Iván
Abstract: Transmissibility-based operational modal analysis (TOMA) is a recent research area that has seen its most significant developments over the last two decades. The advantage of this new approach is its independence from the excitation spectrum. All methods developed have been based on Response Transmissibility (RT) functions or Power Spectrum Density Transmissibility (PSDT) functions. The RT-based methods identify modal parameters from various load conditions and the PSDT-based methods use a single load condition by combining multiple reference outputs. This work proposes a unified concept for TOMA that relates the scalar RT and PSDT functions. This new concept shows that scalar PSDT functions combine n RT functions due to a single load. Two applications emerge from the unified concept: a) the matrix representation permits to identify modal parameters (natural frequencies, damping ratios and mode shapes) from PSDT functions in only one load condition, b) a procedure based on the joint diagonalization of matrices with PSDT functions from different load conditions allows the identification of RT functions. A numerical simulation and actual field data were used to assess the applications of unified concept. The results demonstrate the capacity of new concept to estimate modal parameters and RT functions of structures in operations conditions.